Characteristics of suicidal ideation that predict the transition to future suicide attempts in adolescents. (15th May 2014) - Miranda, Regina; Ortin, Ana; Scott, Michelle; Shaffer, David
<x xml:space="preserve">Abstract</x> Background The present study sought to examine characteristics of suicidal ideation (SI) that predict a future suicide attempt (SA), beyond psychiatric diagnosis and previous SA history. Methods Participants were 506 adolescents (307 female) who completed the Columbia Suicide Screen (CSS) and selected modules from the Diagnostic Interview Schedule for Children (C‐DISC 2.3) as part of a two‐stage high school screening and who were followed up 4–6 years later to assess for a SA since baseline. At baseline, participants who endorsed SI on the CSS responded to four questions regarding currency, frequency, seriousness, and duration of their SI. A subsample of 122 adolescents who endorsed SI at baseline also completed a detailed interview about their most recent SI. Results Thinking about suicide often (OR = 3.5, 95% CI = 1.7–7.2), seriously (OR = 3.1, 95% CI = 1.4–6.7), and for a long time (OR = 2.3, 95% CI = 1.1–5.2) were associated with a future SA, adjusting for sex, the presence of a mood, anxiety, and substance use diagnosis, and baseline SA history. However, only SI frequency was significantly associated with higher odds of a future SA (OR = 3.6, 95% CI = 1.4–9.1) when also adjusting for currency, seriousness, and duration. Among ideators interviewed further about their most recent SI, ideating 1 hr or more (vs. less than 1 hr) was associated with a future SA (OR = 3.6, 95% CI = 1.0–12.7), adjusting for sex, depressive symptoms, previous SA history, and other baseline SI characteristics, and it was also associated with making a future SA earlier. Conclusions Assessments of SI in adolescents should take special care to inquire about frequency of their SI, along with length of their most recent SI.